Oversubscribed, undersubscribed, dan Initial Public Offering (IPO) saham Syariah di Indonesia: (Studi kasus pada Bursa Efek Indonesia) - Lalu Ahmad Ramadani (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2020)
The goal of this study was to determine the factors that contribute to the Oversubscribed and Undersubscribed phenomena in initial public offerings of stocks (IPO). This is a descriptive qualitative study that employs a literature review approach. The study discovered that the Signaling Theory, Shariah Compliance Status, Corporate Image, Expansive Companies, and Corporate Financial Performance all contributed to the occurrence of Oversubscribed and Undersubscribed IPO shares. Given these circumstances, investors will respond positively to the offering of the company's shares. When a firm launches an Initial Public Offering, this will result in the formation of the phenomenon of oversubscriptions or undersubscriptions.